RETRACTED: The impact of swimming classes on restoring psychological comfort of University students - M Payer Juvens Li; Ivanova Anna; Ryzhkin Nikolay; Savchenko Yulia; Jiayang Meng (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001